2016
DOI: 10.1111/bjhp.12207
|View full text |Cite
|
Sign up to set email alerts
|

Attentional and interpretive bias towards illness‐related information in chronic fatigue syndrome: A systematic review

Abstract: Some people with CFS have biases in the way they attend to and interpret somatic information. Such cognitive processing biases may maintain illness beliefs and symptoms in people with CFS. This review highlights methodological issues in experimental design and makes recommendations to aid future research to forge a consistent approach in cognitive processing research. Statement of contribution What is already known on this subject? Studies based on self-report measures suggest negative illness representations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 80 publications
2
42
0
Order By: Relevance
“…Several decades of research in clinical psychology have identified that how people process incoming information, specifically having an attentional bias (AB) to threatening information (AB) and a bias to interpret ambiguous information in a negative way (interpretation bias), plays a central role in the onset and maintenance of anxiety and depression (Beck, 2002;Beck & Clark, 1997;MacLeod, Mathews, & Tata, 1986;Mathews & MacLeod, 2005;Mogg, Mathews, & Eysenck, 1992;Wilson, MacLeod, Mathews, & Rutherford, 2006). Within health psychology, there is burgeoning interest in applying these experimental methods to assess potential cognitive processing biases in physical health conditions, such as chronic pain (Pincus & Morley, 2001;Schoth, Nunes, & Liossi, 2012), chronic fatigue syndrome (Hughes, Hirsch, Chalder, & Moss-Morris, 2016), irritable bowel syndrome and cancer (Chan, Ho, Tedeschi, & Leung, 2011) as well as health behaviours such as eating (Beard, Sawyer, & Hofmann, 2012;Dobson & Dozois, 2004;van Beurden, Greaves, Smith, & Abraham, 2016), smoking (Bradley, Mogg, Wright, & Field, 2003), and alcohol use (Field, Mogg, & Bradley, 2005;Wiers, Eberl, Rinck, Becker, & Lindenmeyer, 2011). Experimental research in these areas could inform theoretical development by enabling access to levels and types of information processing that may underpin unhelpful illness representations and influence health behaviours (Sheeran et al, 2016).…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 2 more Smart Citations
“…Several decades of research in clinical psychology have identified that how people process incoming information, specifically having an attentional bias (AB) to threatening information (AB) and a bias to interpret ambiguous information in a negative way (interpretation bias), plays a central role in the onset and maintenance of anxiety and depression (Beck, 2002;Beck & Clark, 1997;MacLeod, Mathews, & Tata, 1986;Mathews & MacLeod, 2005;Mogg, Mathews, & Eysenck, 1992;Wilson, MacLeod, Mathews, & Rutherford, 2006). Within health psychology, there is burgeoning interest in applying these experimental methods to assess potential cognitive processing biases in physical health conditions, such as chronic pain (Pincus & Morley, 2001;Schoth, Nunes, & Liossi, 2012), chronic fatigue syndrome (Hughes, Hirsch, Chalder, & Moss-Morris, 2016), irritable bowel syndrome and cancer (Chan, Ho, Tedeschi, & Leung, 2011) as well as health behaviours such as eating (Beard, Sawyer, & Hofmann, 2012;Dobson & Dozois, 2004;van Beurden, Greaves, Smith, & Abraham, 2016), smoking (Bradley, Mogg, Wright, & Field, 2003), and alcohol use (Field, Mogg, & Bradley, 2005;Wiers, Eberl, Rinck, Becker, & Lindenmeyer, 2011). Experimental research in these areas could inform theoretical development by enabling access to levels and types of information processing that may underpin unhelpful illness representations and influence health behaviours (Sheeran et al, 2016).…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…The chronic pain literature, in particular, has employed these experimental methods to test the role of hypervigilance to pain (Crombez, Van Ryckeghem, Eccleston, & Van Damme, 2013) as well as pain-related interpretations of ambiguous information (Schoth & Liossi, 2016). Experimental research has begun to be carried out in other long-term conditions such as chronic fatigue syndrome (CFS) (Hughes et al, 2016), irritable bowel syndrome (Afzal, Potokar, Probert, & Munaf o, 2006;Chapman & Martin, 2011;Tkalcic, Domijan, Pletikosic, Setic, & Hauser, 2014), and fear of cancer recurrence (Butow et al, 2015;Custers et al, 2015;DiBonaventura, Erblich, Sloan, & Bovbjerg, 2010;Miles, Voorwinden, Mathews, Hoppitt, & Wardle, 2009). However, to date, evidence for cognitive biases in these areas has been mixed.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…Shortly after its recognition as an illness (6,7), clinical researchers postulated a cognitive behavioural model of CFS that hypothesised that CFS symptoms are perpetuated by the patients' cognitive and behavioural responses to the illness (8,9). Some of the unhelpful cognitive responses in patients with CFS include excessive focusing on fatigue symptoms (10), and catastrophic interpretations of symptoms which involves worrying about worst-case potential consequences (11). These cognitive responses are also associated with behavioural responses in CFS patients, which include reducing or avoiding activities to alleviate fatigue (12,13), or alternating between high levels of activity when feeling well and resting excessively in response to symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…CFS cases with depression involve more inappropriate cognitions and behaviors (Cella, White, Sharpe, & Chalder, 2013). However, a recent review on CFS emphasized cognitive biases in processing information related to the disorder's symptoms regardless of anxiety and depression symptoms, attentional and interpretive biases from the effort of assimilating and organizing the information on the illness (Hughes, Hirsch, Chalder, & Moss-Morris, 2016). All in all, in this study we referred to a component of expectation which could have a different function in outset and maintenance of general fatigue symptoms.…”
Section: Discussionmentioning
confidence: 88%